Financial Literacy based on Education, Income, Future Time Perspective (Pusat Riset dan Inovasi Nasional, 2026)
For senior high school students and undergraduate students, financial literacy becomes increasingly important because it helps them understand about savings, investment, and debt. According to the 2024 Financial Services Authority Survey, the level of financial literacy among this group is lower than the national average and ranks second lowest, behind the group of unemployed individuals, who are the lowest. This research aims to examine and analyze the influence of age, gender, education, and income on future time perspective and financial literacy, as well as to influence future time perspective on financial literacy. This study uses a quantitative approach with a survey method. Data were collected through questionnaires distributed via Google Form. Sampling was conducted using purposive sampling technique with the criteria being Indonesian citizens who work as senior high school students and undergraduate students from various locations. The total number of respondents collected was 325 respondents. Data analysis was conducted using Structural Equation Modelling (SEM) techniques with AMOS software. The research results indicate that age and gender do not influence the future time perspective and financial literacy. In contrast, education and income have a positive effect on the future time perspective and financial literacy. The future time perspective was found to have a mediating effect on the influence of education and income on financial literacy. As a theoretical contribution, this research successfully found the influence of education on future time perspective. Furthermore, this study found that future time perspective partially mediate the influence of education and income on financial literacy. Practically, the researchers recommend that senior high school and undergraduated students can improve their financial literacy by focusing on the opportunities available in the future, supported by education and income. In short, students can gradually improve their financial literacy by integrating knowledge, skill, practical experience with money, and financial goals.